Programming MapPoint in .NET - Thota, Chandu (O'Reilly, 2005)
Interactive web maps generated by MapPoint-Microsoft's popular mapping technology are crucial for businesses in a number of fields, including real estate, package delivery, and commercial air travel. In a word, MapPoint provides businesses with "location." Specifically, it provides an integrated set of products, servers, and services to enable a business to track the precise location of remote assets, thereby reducing operational costs and improving productivity. Whether the asset is a truck, a taxi, or even a field rep, MapPoint can tell you exactly where it is at any time. Programming MapP